Penerapan Kompres Aloevera untuk Menurunkan Suhu Tubuh pada Pasien Anak dengan Demam Tifoid - Eni Esmariah; Regina Natalia; Made Tantra Wirakusuma; Fasida Dharma Yudastoro (PPNI UNIMMAN, 2026)
Typhoid fever is an infectious disease caused by Salmonella typhi. Transmission can occur through air or food contaminated with the urine and feces of typhoid sufferers, such as air used for drinking, cooking, and washing food. Symptoms of typhoid fever include a prolonged high fever, defined as an elevated body temperature of >37.5°C. Other symptoms can include fatigue, nausea, abdominal pain, constipation or diarrhea, and headache. This study aimed to treat children with typhoid fever. The method used was a case study of a five-year-old child with typhoid fever who was hospitalized for four days. The results showed that the child had fever, obesity, and decreased appetite. The child's problem was hypothermia, while cooling interventions were used to manage hypothermia, and one of the cooling procedures performed was the application of aloe vera compresses. The evaluation results showed that the hyperthermia resolved after four days of hospitalization. Based on this study, it is hoped that patients and their families can independently apply aloe vera compresses to treat hypothermia in children.